Photoelectrochemical Cerium Catalysis via Ligand-to-Metal Charge Transfer: A Rising Frontier in Sustainable Organic Synthesis - Wang, Yuying; Liu, Siyuan; Han, Jiangsheng; Wang, Ling; Chen, Jianbin (Synthesis, 2023)
Photoelectrochemical cerium catalysis is an emerging and rapidly developing strategy in organic synthetic. A sustainable platform is being constructed by combining the concerted energy transfer from light and electricity to cerium with the ligand-to-metal charge transfer of excited state CeIV species. With this powerful strategy, hard to oxidized substrates can be activated under mild conditions, contributing to broad functional group compatibility. Such as, carboxylic acids, alcohols, and the Cl anion can deliver the corresponding radicals via formal single electron transfer (SET) with a low oxidation potential. Further cooperation with other synthetic strategies, including alkoxy radical promoted hydrogen atom transfer (HAT) and β-scission, leads to the functionalization of inert C(sp3)–H, Si–H, and C–C bonds via a mild radical pathway. In this review, recent advances in photoelectrochemical cerium catalysis are described. More importantly, as this field features some unique advantages, but is rarely explored, we hope chemists will pay more attention to this catalytic system.1 Introduction2 Activation of Carboxylic Acids3 Activation of Alcohols3.1 Alkoxy Radical Involved Hydrogen Atom Transfer3.2 Alkoxy Radical Promoted β-Scission4 Formal Single-Electron Oxidation of Cl Anion5 Conclusions and Outlook
Keywords: Ce catalysis; photoelectrochemistry; CeIII/CeIV redox pair; photoinduced LMCT; single electron transfer